(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Dalits, the so called marginalized segments of the India have been looming large in the creative consciousness of Indian writer since 1960 when it was initially noticed in Marathi literature. Dalit literature has today taken substantial shape in a variety of Indian languages such as Gujarati, Kannada, Telugu, Punjabi, Tamil, Hindi and Malayalam. A large number of these texts are translated for the benefit of a wider audience within and outside India. Telling literary depictions of the exercise of discrimination, violence and poverty of these suppressed groups have gained special importance on recent times and Dalit literature has acquired a distinct character of its own.